Antibacterial Activity of Ethyl Acetate Fraction of Butterfly Pea Flower (Clitoria ternatea) Against Aeromonas hydrophila in vitro - Aprilyanti, Salsabila; Andayani, Sri; Rahardjo, Seto Sugianto Prabowo (JSMARTech: Journal of Smart Bioprospecting and Technology, 2025)
Aeromonas hydrophila is a pathogenic bacterium responsible for significant losses in freshwater aquaculture. In response to the growing issue of antibiotic resistance, this study examined the antibacterial activity of the ethyl acetate fraction of butterfly pea flowers (Clitoria ternatea) against A. hydrophila in vitro. Extraction was performed using ethyl acetate, followed by Thin Layer Chromatography (TLC) and column chromatography, which yielded nine fractions. Among them, fraction 5 showed the highest antibacterial activity. Phytochemical screening revealed the presence of alkaloids, tannins, flavonoids, and triterpenoids. The Minimum Inhibitory Concentration (MIC) test revealed that 250 ppm was the lowest effective concentration, while the disk diffusion assay demonstrated that 350 ppm produced the largest inhibition zone (10.03 ± 1.27 mm), which was statistically comparable to that of chloramphenicol (F = 91.34; p < 0.01). Scanning Electron Microscopy (SEM) revealed structural damage to A. hydrophila cells, including membrane disruption and lysis. This study introduces a new approach utilizing the ethyl acetate fraction of C. ternatea, combined with fractionation techniques and SEM imaging, to evaluate antibacterial activity. It offers potential for the development of environmentally friendly natural antibacterial agents for the aquaculture industry Keywords: Clitoria ternatea, Aeromonas hydrophila, ethyl acetate fraction, antibacterial activity.